DEVELOPMENT OF FLY ASH BASED GEOPOLYMER ADSORBENT FOR THE EFFECTIVE REMOVAL OF SURFACTANTS FROM MODEL WASTEWATER - SIYAL, AHMER ALI (2021)
World water resources are polluted due to the release of many pollutants such as surfactants, dyes, heavy metals, and others into water resources. Surfactants are harmful to humans, aquatic animals, and vegetation. Adsorption is the most widely used surfactant removal technique due to its effectiveness, simple operation, and economical. Due to the issues of low adsorption efficiency, cost ineffectiveness, poor selectivity, inefficient regeneration, aggregation, leakage into contact waters and adverse effects on the ecosystem and human associated with existing adsorbents, the demand of a new adsorbent is growing. This study develops a fly ash based geopolymer (FAGP) adsorbent for removing anionic sodium dodecylbenzene sulfonate (SDBS), cationic cetyltrimethylammonium bromide (CTAB), and non-ionic Triton X-100 surfactants from model wastewater.